A desregulamentação financeira nos Estados Unidos da América e sua influência na crise do subprime em 2008 - Hiroi, Beatriz de Araujo (2023)
The main objective of this research is to analyze how the lack of financial regulation at the United States of America was responsible for the subprime crisis in 2008. Through the analysis of the global financial system since the Bretton Woods, it is possible to observe a growing financial deregulation over the years and, adding to it, there is also the growing of financial innovations and the development of new technologies in the market. Meanwhile, all of this was not accompanied by regulatory organizations aiming to protect investors and as analyzed, there was also negligence of public organizations, companies, and financial institutions, resulting in the subprime crisis